Educação Ambiental Crítico-Transformadora via Tema Gerador no estudo de aves: uma abordagem para a conscientização ambiental - Camilo, Maria Fernanda de Souza (Universidade Federal de São Carlos, 2025)
This work proposed the application of Critical-Transformative Environmental Education through the Generator Theme approach, resulting in the study of bird ecology as a curricular and teaching-learning axis within the context of a public state school in a municipality in the interior of São Paulo. To this end, an action research methodology was used, grounded in the Organizational Moments of environmental practices via generative themes. Through active listening to the students and an analysis of their conceptions about the environment, a gap was identified between popular knowledge and the scientific understanding essential for citizen environmental education. The focus on bird ecology made it possible to explore biological, ecological, and social content, valuing students' concrete reality and promoting critical reflection on their relationship with the environment. The research revealed that, despite the constant presence of birds in people’s daily lives, their ecological role is often overlooked in the school setting. This work highlights the importance of pedagogical practices that break away from traditional models and prioritize the collective construction of knowledge, in dialogue with the lived experiences of students.
Critical-Transformative Environmental Education through Driving Themes in the ttudy of birds: an approach to environmental awareness
Keywords: Educação Crítica; Formação Cidadã; Paulo Freire; Criticidade; Ensino de Ciências; Critical Education; Citizenship Education; Critical Thinking; Science Teaching; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO; 4. Educação de Qualidade